(untitled) (International relations and international law Journal, 2025)
Kazakhstan-Tajikistan relations hold a significant position within the architecture of regional security and sustainable development in Central Asia. Since the establishment of diplomatic ties in 1993, the two countries have developed a strong and strategic partnership encompassing political, economic, cultural, and educational dimensions. This study offers a comprehensive analysis of the evolution of bilateral cooperation, highlighting major achievements, current challenges, and prospects for further development. Special attention is given to the legal framework, alliance-building mechanisms, transportation and logistics, energy and water security, trade imbalances, and humanitarian exchanges. The theoretical and methodological framework – drawing from regionalism, neorealism, institutionalism, and neoclassical realism – enables a multidimensional understanding of Kazakhstan – Tajikistan relations as part of broader regional and international processes. In the context of increasing global challenges such as instability in neighboring regions, climate change, and transboundary threats, strengthening bilateral cooperation between Kazakhstan and Tajikistan becomes a crucial factor in ensuring security and sustainable development across Central Asia. Keywords: Kazakhstan, Tajikistan, Central Asia, diplomatic relations, foreign policy, bilateral cooperation, trade and economic partnership, regional cooperation and security.